1970
DOI: 10.1016/0021-9290(70)90059-x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of cranial bone

Abstract: Samples of human and Macaca mularta cranial bone have been tested quasistatically in tension, compression, simple shear, and torsion. The results of these experiments have been analyzed, taking into account observed anisotrophies and varying structures. Statistical correlations of properties have been made with density and a model proposed that summarizes these results. The cranial bones appear to be transversely isotropic and they are generally much stronger and stiffer in the transverse or tangent to the sku… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
152
4
3

Year Published

1980
1980
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 380 publications
(171 citation statements)
references
References 9 publications
6
152
4
3
Order By: Relevance
“…All materials used in this model are considered to be homogeneous, isotropic, and linearly elastic. The material properties are listed in Table 1 [12][13][14][15][16].…”
Section: Methodsmentioning
confidence: 99%
“…All materials used in this model are considered to be homogeneous, isotropic, and linearly elastic. The material properties are listed in Table 1 [12][13][14][15][16].…”
Section: Methodsmentioning
confidence: 99%
“…Several studies (Evans and Lissner, 1957;McElhaney et al, 1970;Evans, 1973) have described mechanical characteristics of the cranial vault bone. These studies focused on mechanical tests of structural features by using specimens that included both cortical tables and the diploë.…”
mentioning
confidence: 99%
“…Despite the limitations of a two dimensional (2D) analysis this approach has been extensively used for simulation of machining for decades, in the field of metal and composite cutting. Simulation of orthogonal cutting has allowed the development of efficient models, with low computational cost, able to predict variables related to interface contact or surface integrity, see for instance recent works by the authors Tai et al (2013);Wood (1971);Cezayirlioglu et al (1985); Davy and Connolly (1982); Evans and Lissner (1957);McElhaney et al (1970); Voor et al (1997); Johnson and Rapoff (2007); Kasiri et al (2010); Martin and Boardman (1993); Li et al (2013b); Pithioux et al (2002); Katz et al (1984); Li et al (2014).…”
Section: Orthogonal Cuttingmentioning
confidence: 99%
“…Elastic properties of the human skull bone were based on the results of McElhaney et al (1970) who found that the elastic constants of skull bone do not vary with direction within the plane of the skull surface. Elastic isotropy was used to represent human skull cortical bone (also in the outer cortical layer in the direction normal to the surface).…”
Section: Fe Assuming Isotropic Behaviourmentioning
confidence: 99%
See 1 more Smart Citation